Time point of nocturnal trough systolic blood pressure as an independent predictor of cardiovascular events. Issue 3 (3rd February 2022) - Zhu, Jing; Hao, Xiwa; Tang, Hefei; Xu, Jie; Wang, Anxin; Zhang, Xiaoli; Wang, Yongjun
Abstract: Nocturnal trough systolic blood pressure (NTSBP) and Time Point of Nocturnal Trough Systolic Blood Pressure (T‐NTSBP) were important parameters of nocturnal blood pressure, the predictive values of which are unclear for stroke outcome. This study aimed to examine the relationship between NTSBP/T‐NTSBP and stroke outcome. The authors used data from a nationwide ambulatory blood pressure monitoring cohort study conducted in China, which recruited 2348 ischemic stroke and transient ischemic attack (TIA) patients. NTSBP was defined as the lowest SBP during nighttime (22:00–6:00), and T‐NTSBP was defined as the corresponding time point of NTSBP. The associations between NTSBP/T‐NTSBP and stroke outcome (stroke recurrence and combined vascular event [CVE]) at 90 days or 1 year were analyzed using cox regression models. According to NTSBP classified by quartile, hazard ratio (HR) with 95% confidence interval (CI) for NTSBP quartile 4 (>129 mm Hg) was 2.727 (1.148–6.478) for CVE at 90‐day, compared with quartile 1 (≤102 mm Hg). However, an attenuated association between NTSBP and CVE was observed at 1 year. In addition, we observed the group of T‐NTSBP at 4:00–6:00 had a lowest CVE incidence at 90 days among four groups (22:00–23:59, 00:00–1:59 2:00–3:59, 4:00–6:00). After multivariable adjustment, T‐NTSBP was significantly associated with CVE incidence at 90 days (T‐NTSBP at the 4:00–6:00 versus the 22:00–23:59 group: HR, 0.433; 95%CI, 0.190–0.986), independent of NTSBP and average nocturnal SBP. Both of NTSBP and T‐NTSBP were important predictors for short‐term cardiovascular risk in ischemic stroke and TIA patients.